Scientific American. – 1865. – Vol. 13, № 13 - б/а (New York. Munn & Company, 1865)
A weekly journal of practical information in art, science, mechanics, chemistry and manufactures.
Scientific American. Vol. 13, N 1–16. – New York, 1865. – P. 1–254.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Economic history; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; Research Subject Categories::NATURAL SCIENCES::Physics; Research Subject Categories::NATURAL SCIENCES::Chemistry; September 23, 1865; Recent American Patents; Patents; Improved Gang Plow; Davenport’s Gang Plow; New Mineral; Manufacture of Ultramarine; Economic Magnesium Light; Brainard’s Parallel Traversing Vise; Improved Velocipede; The “Rantoone”; New Method of Photo-relieve Printing; A Natural Flying Machine; Percival’s Self-regulating Faucet; Improved Electro-Magnet; Bradley’s Receiving Magnet; Markland’s Coal Scuttle